Evaluasi Program Latihan Club Futsal Mitra FC U-20 Kabupaten Sumenep - Hamdan Wajdy Kusuma; Heri Wahyudi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The training program in sports is the most important thing in achieving an achievement that is the main target of each team. This factor is none other than the existence of long-term coaching and various training programs. This factor is none other than the existence of long-term coaching and various training programs. A coach provides a variety or varied training program to be evaluated at the end of the training. The purpose of the evaluation itself is to correct mistakes from either the training program or the athlete. The research method of evaluating the CIPP program (context, input, process, product) using quantitative and qualitative descriptive methods. The results of the research on the Evaluation of the Coaching of the Futsal Club Mitra Fc U-20 Sumenep Regency, received a score of 3.35 which is categorized as very good. 3) Process The results of the research on the Evaluation of the Futsal Club Mitra Fc U-20 Sumenep Regency, received a score of 3.35 which is in the very good category. 4) Product The results of the research on the Evaluation of the Futsal Club Mitra Fc U-20 Sumenep Regency, received a score of 3.31 which is in the very good category. Based on the results of the research that has been carried out, there are the following conclusions: 1. Aspects of context, input, process, product. With good performance indicators, excellent efforts, and good results.